REAL TIME PCR IDENTIFICATION FOR TARGET ADJUNCTIVE ANTIBIOTIC THERAPY OF SEVERE CHRONIC PERIODONTITIS. PART I - CLINICAL RESULTS. - Kamen Kotsilkov; Christina Popova (Peytchinski Publishing, 2014)
INTRODUCTION: The periodontal pathology is of great social importance due to the vast distribution in the human population. The adjunctive antibiotic administration could improve the healing in such cases but the latest data of the continuingly growing antibiotic resistance requires more precise approaches of antibiotic selection. The contemporary molecular diagnostic methods could offer the required precision for the microbiological identification in order to achieve better control of the periodontitis. OBJECTIVE: The aim of this study is to compare the microbiological effectiveness of adjunctive antibiotic administration with the mechanical periodontal therapy. METHODS: 30 patients with severe chronic periodontitis were enrolled in this study and were divided in 3 groups: Control group - with mechanical debridement only. Test group 1 - with combined adjunctive antibiotic administration using Amoxicillin+ Metronidazole. Test group 2 - with target antibiotic administration according to the resuts from the Real Time PCR identification. RESULTS: A considerable improvement of the periodontal status was reported in all treatment groups. The most positive results were in the group with target antibiotic administration were all tested clinical parameters showed the best improvement with statistically significant changes in sites with PD<3mm, PD 5-7mm, PD>7mm and CAL>5mm. CONCLUSION: The adjunctive antibiotic administration demonstrates better clinical effectiveness concerning the reduction of the severely affected sites in cases with severe generalized chronic periodontitis compared to the mechanical therapy alone. From all examined groups the target approach has statistically significant better results. These results suggest that this approach is recommended in cases with high prevalence of deep pockets.